Larangan Pornografi Dalam Undang-Undang nomor 44 Tahun 2008 tentang Pornografi (Perspektif Asas Legalitas) - Wibisono, Muhammad Iqbal; Fawaid, Bahrul (Qistie Jurnal Ilmu Hukum, 2021)
Law No. 44 of 2008 concerning Pornography was officially ratified on October 30, 2008. The emergence of this law cannot be separated from public anxiety about pornography cases which are increasingly spreading and consumed by various groups. Ease of access to information either through electronic media or communication media seems to be a 'free space' for the public to enjoy pornographic information or displays. By using a normative approach, the study of the problem is carried out using the flow and workings of the first and third types of doctrinal law research from Terry Hutchinson, because they are in accordance with the research problem and the purpose of this paper. This study aims to analyze whether the prohibition of pornography in Law no. 44 of 2008 following the principles of legality? It can be seen that the principle of legality actually has the main goal of protecting the dignity of a person from the arbitrariness of the authorities in applying the law. In the matter of pornography, the regulation must be clear, so as not to cause noise in its implementation. Given the diversity that exists in Indonesia, the criteria for pornography can vary. Thus, the state through its law enforcement officers must pay attention to local cultural factors. For this reason, it is necessary to make legal rules that can provide an umbrella for this diversity so that it can be a guide for judges in particular to assess whether an act that is considered to violate the law is something that is not against the law.